2021
DOI: 10.1111/tran.12503
|View full text |Cite
|
Sign up to set email alerts
|

Urbanisation and the shifting conditions of the state as a territorial‐political community: A study of the geographies of political efficacy

Abstract: This paper contributes to recent debates on the geographies of discontent and the rise of populism as reflective of increasing territorial inequalities and a deepening divide between prosperous urban cores and declining peripheries (McCann, 2020;Rodríguez-Pose, 2018). While unequal economic geographies, as well as claims related to the loss of territorial sovereignty (Menon & Wager, 2020), are essential to understanding the current geographies of discontent, in this paper we suggest a complementary explanation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 80 publications
(122 reference statements)
1
3
0
Order By: Relevance
“…This study also found that small towns and rural areas demonstrated lower levels of external efficacy than cities (suburban areas were indistinguishable from cities), which implies that small‐town and rural residents tend to feel that government is not responsive to their concerns. This finding is in line with similar earlier studies in Europe (see e.g., del Horno et al., 2023; Luukkonen et al., 2022). However, internal efficacy did not exhibit such a strong difference, which may mean that the urban–rural divide is linked more closely to government responsiveness than to people's own understanding of political issues.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This study also found that small towns and rural areas demonstrated lower levels of external efficacy than cities (suburban areas were indistinguishable from cities), which implies that small‐town and rural residents tend to feel that government is not responsive to their concerns. This finding is in line with similar earlier studies in Europe (see e.g., del Horno et al., 2023; Luukkonen et al., 2022). However, internal efficacy did not exhibit such a strong difference, which may mean that the urban–rural divide is linked more closely to government responsiveness than to people's own understanding of political issues.…”
Section: Discussionsupporting
confidence: 93%
“…Some scholars have explored this topic outside of American society. For example, Luukkonen and others (2022) compared European societies and found that external political efficacy is weaker in rural settings and in regions with low gross domestic products and declining populations. However, much is still unknown about this relationship especially in American political and historical contexts.…”
Section: Political Efficacy and The Rural–urban Divide In The America...mentioning
confidence: 99%
See 1 more Smart Citation
“…Such a development also has profound implications for the territorial political community of the state and its citizen-subjects in the sense that city-regionalist discourse delimits the space of public deliberation and legitimate public issues to specifically "urban" issues concerning the economic competitiveness of selected urban locales (Sirviö & Luukkonen 2020). In turn, this influences growing regional discontent (Dijkstra et al 2020;Larsson et al 2021;Luukkonen et al 2022;McCann 2020;Rodríguez-Pose 2018).…”
Section: The Geographies Of Depoliticizationmentioning
confidence: 99%